Webové MVC rámce na platformě Java - Hybášek, Michal (Vysoké učení technické v Brně. Fakulta informačních technologií)
Tato práce se zabývá architekturou Model-View-Controller. Vysvětluje princip, model, použití a výhody architektury. Dále představuje nejznámější webové rámce nad platformou Java, které této architektury využívají. Jsou to rámce Apache Struts, Tapestry a Spring. V práci je popsán princip rámců a práce s nimi. Součástí práce jsou i jednoduché aplikace využívající těchto rámců. Práce podává návod jak tyto aplikace vytvořit. Popisuje a srovnává nejnovější verze těchto nástrojů. Rámci Spring se zabývá ve větší míře, popisuje jeho základní principy a moduly se zvýšeným zaměřením na modul Web MVC.

This master thesis deals with an architecture Model-View-Controller. It explains the principle, model, usage and benefits of an architecture. Futhure more, it presents the best known web frameworks on Java platform which derive benefit from this architecture. There are frameworks like Apache Struts, Tapestry and Spring. In my thesis, the principles of framworks and the work with them are described. Concerning another part of my thesis, there are simple applications which use this frameworks. The work gives instructions to make these applications. It describes and compares the latest versions of these tools. It deals more with framework Spring, describes its elementary principles and modules with enhanced sight to Web MVC of Spring.
Web MVC Frameworks on the Java Platform
Keywords: Java; JEE; Model-View-Controller; MVC rámec; Struts; Tapestry; Spring; anotace; Java; JEE; Model-View-Controller; MVC framework; Struts; Tapestry; Spring; annotations